Graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode and preparation method thereof
By preparing graphene-like two-dimensional Fe2O3 nanosheets/ZnO nanorod composite photoelectrodes, the shortcomings of existing ZnO photoelectrodes in solar spectrum utilization are solved, and more efficient photocharge transmission and catalytic performance are achieved.
Patent Information
- Application Number
- CN202111151361.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-29
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-09-29
AI Technical Summary
The existing ZnO photoelectrodes have problems with low visible light utilization and serious photocorrosion in solar spectrum utilization, and the composite photoelectrode lacks a reasonable design, resulting in hindered charge transfer.
The preparation method of graphene-like two-dimensional Fe2O3 nanosheets/ZnO nanorod composite photoelectrode is adopted. By preparing ZnO nanorod arrays and graphene-like two-dimensional Fe2O3 nanosheets, the transmission path of photogenerated charges is improved by combining the "one-dimensional + two-dimensional" interface design of the two.
The catalytic performance and photoresponse degree of photoelectrode are improved, the charge transmission path of photoelectrode is optimized, and the utilization efficiency of solar energy spectrum is enhanced.
Smart Images

Figure CN115872497B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nanomaterial photoelectrochemistry, and in particular to a graphene-like two-dimensional Fe 2 O 3 Preparation method of nanosheet / ZnO nanorod composite photoelectrode. Background Art
[0002] With the rapid development of the world economy and scientific research technology, environmental problems such as air and water pollution caused by organic pollutant emissions have become the main factors restricting the economic and social development of countries around the world. Photoelectrochemical technology has made relatively mature development in catalytic decomposition of water, degradation of organic pollutants and construction of sensor devices. Among them, photoelectrocatalytic water treatment technology has been listed by the US Environmental Protection Agency as the most promising high-tech environmental protection technology.
[0003] As a mature wide bandgap semiconductor material, ZnO has been extensively researched and developed, but its low visible light utilization rate and severe photocorrosion have greatly limited its use in the solar spectrum. 2 O 3 Semiconductors have the advantages of narrow band gap (1.8-2.2eV) and good stability, and are often used to modify ZnO semiconductors, which can effectively extend the light response to the visible light region. Due to the lack of reasonable design for composite photoelectrodes, the matching degree of material dimensions is usually ignored, resulting in problems such as blocked charge transfer. Summary of the invention
[0004] The present invention is carried out to solve the above problems and aims to provide a graphene-like two-dimensional Fe 2 O 3 Preparation method of nanosheet / ZnO nanorod composite photoelectrode.
[0005] The present invention provides a graphene-like two-dimensional Fe 2 O 3 The method for preparing the nanosheet / ZnO nanorod composite photoelectrode has the following characteristics and comprises the following steps:
[0006] Step 1, preparing ZnO nanorod arrays.
[0007] Step 2: Preparation of graphene-like two-dimensional Fe 2 O 3 Nanosheets.
[0008] Step 3: Using ZnO nanorod arrays and graphene-like two-dimensional Fe 2 O 3 Preparation of graphene-like two-dimensional Fe nanosheets 2 O 3Nanosheet / ZnO nanorod composite photoelectrode.
[0009] In the graphene-like two-dimensional Fe 2 O 3 The method for preparing the nanosheet / ZnO nanorod composite photoelectrode may also have the following characteristics: wherein step 1 specifically includes the following steps:
[0010] Step 1-1, placing fluorine-doped tin oxide (FTO) conductive glass in acetone, anhydrous ethanol and ultrapure water for ultrasonic cleaning for 25 to 35 minutes and then drying.
[0011] Step 1-2, dissolving zinc acetate in anhydrous ethanol to obtain a ZnO seed layer solution, lightly coating the ZnO seed layer solution on the conductive surface of the FTO conductive glass, and placing the coated FTO conductive glass in a muffle furnace, annealing at 400° C. to obtain a FTO conductive glass with a ZnO seed layer.
[0012] Step 1-3, mixing zinc nitrate hexahydrate solution and hexamethylenetetramine solution in equal proportions to obtain a ZnO precursor solution, placing FTO conductive glass with a ZnO seed layer and the ZnO precursor solution into a hydrothermal reactor, placing the hydrothermal reactor into an oven for hydrothermal reaction, taking out the FTO conductive glass after cooling to room temperature, cleaning and drying, and obtaining a ZnO nanorod array.
[0013] In the graphene-like two-dimensional Fe 2 O 3 The method for preparing the nanosheet / ZnO nanorod composite photoelectrode may also have the following characteristics: wherein, in step 1-2, the concentration of the ZnO seed layer solution is 0.045-0.055M.
[0014] In the graphene-like two-dimensional Fe 2 O 3 The preparation method of the nanosheet / ZnO nanorod composite photoelectrode can also have the following characteristics: wherein, in steps 1-3, the concentrations of the zinc nitrate hexahydrate solution and the hexamethylenetetramine solution are both 0.05 M, the reaction temperature of the hydrothermal reaction is 90-94° C., and the reaction time is 9.5-10.5 h.
[0015] In the graphene-like two-dimensional Fe 2 O 3 The method for preparing the nanosheet / ZnO nanorod composite photoelectrode may also have the following characteristics: wherein step 2 specifically includes the following steps:
[0016] Step 2-1, placing the hematite raw material into a NN dimethylformamide solution, and using an ultrasonic-assisted liquid phase exfoliation technique to continuously perform ultrasonic exfoliation for two days to obtain an exfoliated stock solution.
[0017] Step 2-2, pour the stripped stock solution into a centrifuge tube for centrifugation, and separate the two-dimensional Fe 2 O 3 The sheet suspension was decanted.
[0018] Step 2-3, two-dimensional Fe 2 O 3 The sheet suspension was transferred to a circulating water vacuum pump for filtration to obtain graphene-like two-dimensional Fe 2 O 3 Nanosheets.
[0019] In the graphene-like two-dimensional Fe 2 O 3 The method for preparing the nanosheet / ZnO nanorod composite photoelectrode may also have the following characteristics: wherein, in step 2-2, the centrifugal condition is 7000 rpm / min.
[0020] In the graphene-like two-dimensional Fe 2 O 3 The method for preparing the nanosheet / ZnO nanorod composite photoelectrode may also have the following characteristics: wherein step 3 specifically includes the following steps:
[0021] Step 3-1: Graphene-like two-dimensional Fe 2 O 3 The nanosheets were redispersed in NN dimethylformamide solution and the graphene-containing two-dimensional Fe 2 O 3 The NN dimethylformamide solution of the nanosheet layer is coated on the ZnO nanorods, and the coating is repeated several times and dried until the surface of the ZnO nanorods turns into a uniform brick red, thereby obtaining a graphene-like two-dimensional Fe 2 O 3 Nanosheets of ZnO nanorods.
[0022] Step 3-2: Coating the graphene-like two-dimensional Fe 2 O 3 The ZnO nanorods of the nanosheet layer were placed in a muffle furnace and annealed at 200°C to obtain a graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode.
[0023] The present invention also provides a graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode having the following characteristics:
[0024] The graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode of the present invention is a photoelectrode obtained by utilizing the graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode preparation method of the present invention.
[0025] Functions and Effects of the Invention
[0026] According to the graphene-like two-dimensional Fe 2 O 3 The preparation method of nanosheet / ZnO nanorod composite photoelectrode is to first prepare ZnO nanorod arrays and then prepare graphene-like two-dimensional Fe 2 O 3 Nanosheets, and finally ZnO nanorod arrays and graphene-like two-dimensional Fe 2 O 3 Preparation of graphene-like two-dimensional Fe nanosheets 2 O 3 Nanosheet / ZnO nanorod composite photoelectrode. The above process effectively realizes the graphene-like two-dimensional Fe 2 O 3 Preparation of nanosheet / ZnO nanorod composite photoanode, ZnO is in the shape of vertical hexagonal nanorods, and graphene-like two-dimensional Fe 2 O 3 The thickness of the nanosheet is several nanometers, constructing a "one-dimensional + two-dimensional" interface design. The combination of the two improves the transmission path of photogenerated charges and optimizes the catalytic performance of the photoelectrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a graphene-like two-dimensional Fe 2 O 3 Flow chart of the preparation method of nanosheet / ZnO nanorod composite photoelectrode;
[0028] Figure 2 It is a graphene-like two-dimensional Fe 2 O 3 Atomic force microscopy images of nanosheets;
[0029] Figure 3 In the embodiment of the present invention, a graphene-like two-dimensional Fe 2 O 3 Physical picture of ZnO nanorods in nanosheet layer;
[0030] Figure 4 It is a graphene-like two-dimensional Fe 2 O 3 Electron microscope top view of the nanosheet / ZnO nanorod composite photoelectrode;
[0031] Figure 5 In the embodiment of the present invention, FTO conductive glass, ZnO nanorods and graphene-like two-dimensional Fe 2 O 3 X-ray diffraction comparison of nanosheet / ZnO nanorod composite photoelectrode;
[0032] Figure 6 It is a graphene-like two-dimensional Fe 2 O 3 Photocurrent-time curve of the nanosheet / ZnO nanorod composite photoelectrode. DETAILED DESCRIPTION
[0033] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the following embodiments are combined with the accompanying drawings to illustrate a graphene-like two-dimensional Fe 2 O 3 The preparation method of nanosheet / ZnO nanorod composite photoelectrode is described in detail.
[0034] The chemical reagents and instruments used in the following examples are all commercially available.
[0035] In this embodiment, a graphene-like two-dimensional Fe 2 O 3 Preparation method of nanosheet / ZnO nanorod composite photoelectrode.
[0036] Figure 1 It is the graphene-like two-dimensional Fe 2 O 3 Flow chart of the preparation method of nanosheet / ZnO nanorod composite photoelectrode.
[0037] like Figure 1 As shown, the graphene-like two-dimensional Fe 2 O 3 The preparation method of the nanosheet / ZnO nanorod composite photoelectrode comprises the following steps:
[0038] Step S1, preparing a ZnO nanorod array. The specific implementation method is as follows:
[0039] Step S1-1, ultrasonically clean the FTO conductive glass in acetone, anhydrous ethanol and ultrapure water for 30 minutes, test the conductive surface with a multimeter, and place the glass in an oven with the conductive surface facing upward for drying.
[0040] Step S1-2, dissolving zinc acetate in anhydrous ethanol to obtain a ZnO seed layer solution with a concentration of 0.05M, using a pipette to absorb the ZnO seed layer solution, and lightly coating it on the conductive surface of the FTO conductive glass, and placing the coated FTO conductive glass in a muffle furnace, annealing at 400°C, to obtain FTO conductive glass with a ZnO seed layer.
[0041] Step S1-3, a zinc nitrate hexahydrate solution and a hexamethylenetetramine solution, both with a concentration of 0.05M, are mixed in equal proportions to obtain a ZnO precursor solution, and the FTO conductive glass with a ZnO seed layer is placed obliquely on the polytetrafluoroethylene-lined side wall of the hydrothermal reactor with the conductive surface facing downward, and the ZnO precursor solution is poured into the hydrothermal reactor, and the hydrothermal reactor is placed in an oven, and a hydrothermal reaction is carried out at 92° C. for 10 hours. After cooling to room temperature, the FTO conductive glass is taken out, cleaned, and dried to finally obtain a ZnO nanorod array.
[0042] Step S2, preparing graphene-like two-dimensional Fe 2 O 3 Nanosheet layer. The specific implementation is:
[0043] Step S2-1, placing the hematite raw material into a NN dimethylformamide solution, and using an ultrasonic-assisted liquid phase exfoliation technique to continuously perform ultrasonic exfoliation for two days to obtain an exfoliated stock solution.
[0044] Step S2-2, pour the stripped stock solution into a centrifuge tube and centrifuge at 7000 rpm / min to separate the two-dimensional Fe 2 O 3 The sheet suspension was decanted.
[0045] Step S2-3, the two-dimensional Fe 2 O 3 The sheet suspension was transferred to a circulating water vacuum pump for filtration to obtain graphene-like two-dimensional Fe 2 O 3 Nanosheets.
[0046] Figure 2 It is an atomic force microscope image of the graphene-like two-dimensional Fe2O3 nanosheet layer in this embodiment.
[0047] Step S3, using ZnO nanorod arrays and graphene-like two-dimensional Fe 2 O 3 Preparation of graphene-like two-dimensional Fe nanosheets 2 O 3 Nanosheet / ZnO nanorod composite photoelectrode. The specific implementation is:
[0048] Step S3-1, graphene-like two-dimensional Fe2 O 3 The nanosheets were redispersed in NN dimethylformamide solution, and the drop coating technique was used to absorb the graphene two-dimensional Fe 2 O 3 The NN dimethylformamide solution of the nanosheet layer is coated on the ZnO nanorods, and the coating is repeated several times and dried until the surface of the ZnO nanorods turns into a uniform brick red, thereby obtaining a graphene-like two-dimensional Fe 2 O 3 Nanosheets of ZnO nanorods.
[0049] Step S3-2, coating the graphene-like two-dimensional Fe 2 O 3 The ZnO nanorods of the nanosheet layer were placed in a muffle furnace and annealed at 200°C to obtain a graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode.
[0050] Figure 3 In the embodiment of the present invention, a graphene-like two-dimensional Fe 2 O 3 Physical picture of ZnO nanorods in nanosheet layer.
[0051] Depend on Figure 3 It can be seen that the graphene-like two-dimensional Fe 2 O 3 The surface of the ZnO nanorods in the nanosheet layer is obviously brick red, which indicates that the two-dimensional Fe 2 O 3 The nanosheets have been uniformly loaded onto the ZnO nanorods.
[0052] Figure 4 It is an electron microscope top view of the graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode in an embodiment of the present invention.
[0053] Depend on Figure 4 It can be seen that the two-dimensional Fe 2 O 3 The nanosheet layer is only about 1 to 3 nm thick. The ZnO carrier is a ZnO nanorod array with a hexagonal cross section, which grows vertically and uniformly on the entire FTO conductive glass at a high density. In addition, graphene-like two-dimensional Fe 2 O 3 The nanosheets have been successfully connected to the ZnO nanorods and mainly grown on the surface of the ZnO nanorods.
[0054] Figure 5 It is a comparison diagram of X-ray diffraction of FTO conductive glass, ZnO nanorods and graphene-like two-dimensional Fe2O3 nanosheets / ZnO nanorod composite photoelectrodes in the embodiments of the present invention.
[0055] Depend on Figure 5 It can be seen that most of the diffraction peaks in b belong to hexagonal ZnO nanorods (JCPDS 36-1451), and the strongest diffraction peak is located at 34.42°, indicating that the ZnO nanorods grow along the (002) direction. 2 O 3 After the nanosheet, two-dimensional Fe 2 O 3 The diffraction peaks (JCPDS 33-0664) of the graphene-like Fe2O3 phase are not observed, and no other impurity peaks of inorganic iron-containing phases appear, forming a graphene-like two-dimensional Fe2O3 phase with good crystallinity. 2 O 3 Heterostructure of ZnO nanosheets / nanorods.
[0056] Figure 6 It is a photocurrent time curve diagram of the graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode in an embodiment of the present invention.
[0057] Depend on Figure 6 It can be seen that graphene-like two-dimensional Fe 2 O 3 The nanosheet / ZnO nanorod composite photoelectrode has a good light response degree. When the light source is turned on, the photocurrent value instantly reaches the maximum value, and once the light source is turned off, the photocurrent value quickly decreases to a position close to 0, indicating that the graphene-like two-dimensional Fe 2 O 3 The nanosheet / ZnO nanorod composite photoelectrode has excellent photoresponse and photosensitivity.
[0058] Functions and Effects of the Embodiments
[0059] According to the graphene-like two-dimensional Fe 2 O 3 The preparation method of nanosheet / ZnO nanorod composite photoelectrode is to first prepare ZnO nanorod arrays and then prepare graphene-like two-dimensional Fe 2 O 3 Nanosheets, and finally ZnO nanorod arrays and graphene-like two-dimensional Fe 2 O 3 Preparation of graphene-like two-dimensional Fe nanosheets 2 O 3 Nanosheet / ZnO nanorod composite photoelectrode. The above process effectively realizes the graphene-like two-dimensional Fe 2 O 3 Preparation of nanosheet / ZnO nanorod composite photoanode, ZnO is in the shape of vertical hexagonal nanorods, and graphene-like two-dimensional Fe 2 O 3The thickness of the nanosheet is several nanometers, constructing a "one-dimensional + two-dimensional" interface design. The combination of the two improves the transmission path of photogenerated charges and optimizes the catalytic performance of the photoelectrode.
[0060] The above-mentioned embodiments are preferred examples of the present invention and are not intended to limit the protection scope of the present invention.
Claims
1. A method for preparing a graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode, characterized in that: The following steps are involved: Step 1, preparing a ZnO nanorod array; Step 2, preparing graphene-like two-dimensional Fe2O3 nanosheets; Step 2-1, placing the hematite raw material into a NN dimethylformamide solution, and performing ultrasonic stripping for two consecutive days using an ultrasonic-assisted liquid phase stripping technique to obtain a stripped stock solution; Step 2-2, pouring the peeled stock solution into a centrifuge tube for centrifugation, and pouring out the two-dimensional Fe2O3 sheet suspension suspended in the upper layer of the centrifuge tube; Step 2-3, transferring the two-dimensional Fe2O3 sheet suspension to a circulating water vacuum pump for filtration to obtain graphene-like two-dimensional Fe2O3 nanosheets; Step 3, preparing a graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode using the ZnO nanorod array and the graphene-like two-dimensional Fe2O3 nanosheet layer; Step 3-1, re-dispersing the graphene-like two-dimensional Fe2O3 nanosheet layer in a NN dimethylformamide solution, applying the NN dimethylformamide solution containing the graphene two-dimensional Fe2O3 nanosheet layer on the ZnO nanorods by a drop coating technique, repeating the coating multiple times, and drying until the surface of the ZnO nanorods becomes a uniform brick red, thereby obtaining a ZnO nanorod coated with a graphene-like two-dimensional Fe2O3 nanosheet layer; Step 3-2, placing the ZnO nanorod coated with the graphene-like two-dimensional Fe2O3 nanosheet layer in a muffle furnace, and annealing at 200° C. to obtain a graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode, The thickness of the two-dimensional Fe2O3 nanosheet layer is 1-3 nm, and the ZnO carrier is a ZnO nanorod array with a hexagonal cross section, which grows vertically and uniformly on the entire FTO conductive glass with high density.
2. A method for preparing a graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode according to claim 1, Features: Wherein, step 1 specifically includes the following steps: Step 1-1, placing the fluorine-doped tin oxide conductive glass in acetone, anhydrous ethanol and ultrapure water for ultrasonic cleaning for 25 to 35 minutes and then drying; Step 1-2, dissolving zinc acetate in anhydrous ethanol to obtain a ZnO seed layer solution, lightly coating the ZnO seed layer solution on the conductive surface of the fluorine-doped tin oxide conductive glass, and placing the coated fluorine-doped tin oxide conductive glass in a muffle furnace, annealing at 400° C. to obtain a fluorine-doped tin oxide conductive glass having a ZnO seed layer; Step 1-3, mixing zinc nitrate hexahydrate solution and hexamethylenetetramine solution in equal proportions to obtain a ZnO precursor solution, placing the fluorine-doped tin oxide conductive glass with a ZnO seed layer and the ZnO precursor solution into a hydrothermal reaction kettle, placing the hydrothermal reaction kettle into an oven for hydrothermal reaction, taking out the fluorine-doped tin oxide conductive glass after cooling to room temperature, cleaning and drying it, and obtaining a ZnO nanorod array.
3. The method for preparing a graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode according to claim 2, characterized in that: in, In step 1-2, the concentration of the ZnO seed layer solution is 0.045-0.055M.
4. The method for preparing a graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode according to claim 2, characterized in that: in, In step 1-3, the concentrations of the zinc nitrate hexahydrate solution and the hexamethylenetetramine solution are both 0.05 M. The reaction temperature of the hydrothermal reaction is 90-94° C., and the reaction time is 9.5-10.5 h.
5. The method for preparing a graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode according to claim 4, characterized in that: in, In step 2-2, the centrifugal condition is 7000 rpm / min.
6. A graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode, characterized in that: The graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode is the graphene-like two-dimensional Fe2O3 nanosheet / ZnO nanorod composite photoelectrode according to any one of claims 1 to 5.
Citation Information
Patent Citations
Hybrid solar cell with aluminum-doped zinc oxide nanorod as electron transfer layer
CN103474574A
Molybdenum sulfide / ferric oxide composite material and preparation method and application thereof
CN106783201A
Titanium dioxide photoelectrode with three-dimensional crystal facet junction property and preparation and application thereof
CN113189174A